THE NOVEL OF FOR WHOM THE BELL TOLLS - Assist. Lect. Riyadh Mohsen Huwail; Hani Mohammed Saeed Mohammed Ali (Journal of Higher Education and Academic Advancement, 2024)
The conflict loots each character in ''For Whom the Bell Tolls'' of their physical and psychological innocence. Some suffer from physical shock. The story time Spain is limited to four days. Tens of thousands of words and more information have been written by the author. People's minds are chaotic and they often think about things that occurred during wartime while they are experiencing problems. These are random thoughts that don't make sense. In order to allow the reader to empathize with the character and understand how complicated the psychological characters are, the author of this review attempts to convey this ambivalence in an intuitive manner